2005
DOI: 10.1007/s11916-005-0056-x
|View full text |Cite
|
Sign up to set email alerts
|

Opioids for neuropathic pain

Abstract: Whether opioids are effective for neuropathic pain has been a matter of controversy for decades. Within limits, it is clear that opioids in general are effective for neuropathic pain. Furthermore, there is no evidence that opioids are any less effective for neuropathic pain than for non-neuropathic pain, no evidence that opioids are less effective for neuropathic pain than are other medications, and no evidence that one opioid is any more effective than another for neuropathic pain. It remains uncertain whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Yet, the belief that NP is opioid-resistant, as well as concerns over adverse effect profiles and potential for abuse often discourages the use of opioids for NP. Recent systematic reviews (Eisenberg et al, in press;Kalso et al, 2004;Katz and Benoit, 2005) of randomized controlled trials (RCTs) have shown the efficacy of opioids in reducing spontaneous NP. However, little is known about their efficacy for evoked pain.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the belief that NP is opioid-resistant, as well as concerns over adverse effect profiles and potential for abuse often discourages the use of opioids for NP. Recent systematic reviews (Eisenberg et al, in press;Kalso et al, 2004;Katz and Benoit, 2005) of randomized controlled trials (RCTs) have shown the efficacy of opioids in reducing spontaneous NP. However, little is known about their efficacy for evoked pain.…”
Section: Introductionmentioning
confidence: 99%
“…Opioids comprise the most potent analgesic medications and have a broad range of efficacy 7 . Studies have suggested that patients with nociceptive pain are most responsive to opioids 3 , but that a subset of patients with neuropathic pain also demonstrates good response [8][9][10] . It has been suggested that opioid responsiveness represents a continuum, with extensive overlap in the responsiveness of pain that is mediated by nociceptive, neuropathic and mixed mechanisms 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Possible other explanations are loss of receptors due to the lesion, transneuronal degeneration, or receptor mechanisms such as receptor internalization or downregulation [62]. These observations of reduced opioid receptor binding in central pain patients may explain the poor response of these patients to opioid treatment [64].…”
Section: Neurochemical Studiesmentioning
confidence: 99%